Strategi STAI As-Sunnah Tanjung Morawa dalam Menangkal Radikalisme - Hasan Hamzah Lubis (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
Islam is a religion that commands its adherents to always do good, not to damage or even kill other people, but slanted news about Islam is always decorated by irresponsible people; they say Islam is a religion of terrorism and a religion full of violence. Referring to this, the researcher will thoroughly explore the STAI As-Sunnah strategy in countering radicalism, as well as formulate the supporting and inhibiting factors of the strategy. This research is a field research with a descriptive qualitative method carried out at STAI As-Sunnah, the source of data researchers absorb from the head of STAI As-Sunnah, assistant chairman 1 in the field of education, assistant chairman 3 in the field of student affairs, as well as the sections they supervise and the institutions that in collaboration with STAI As-Sunnah. Data collection methods used by researchers are observation, interviews, and documentation. Data analysis and processing was carried out in three steps, namely data reduction, data presentation and data verification. The results of this research explain that the strategies adopted by STAI As-Sunnah are academic and non-academic strategies. The supporting factors for the strategy are: the vision and mission of STAI As-Sunnah, a conducive environment for STAI As-Sunnah, the appointment of lecturers and students and the boarding school system; As for the barrier factors, namely: communication and print media, living environment, family life and school of origin of students.